The Near Witch - Schwab, Victoria (New York : Hyperion, 2011)
Sixteen-year-old Lexi, who lives on an enchanted moor at the edge of the village of Near, must solve the mystery when, the day after a mysterious boy appears in town, children start disappearing.
Keywords: Witches -- Fiction; Villages -- Fiction; Interpersonal relations -- Fiction; Supernatural -- Fiction